Bimbingan Menanamkan Nilai Agama Melalui Kegiatan Praktek Ibadah Di RA Al-Hijrah Desa Hampalit - Eka Nurhalisa; Saudah Saudah; Muzakki Muzakki (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Education is the first foundation that must be given to children. especially religion, which must be instilled in children from early childhood until the child is an adult. The aim of teaching religion is as a rule revealed by God to humans so that humans can live in an orderly, peaceful, dignified and happy world and the hereafter. Because the position of religion is primary or main, religion really needs to be instilled in children from an early age. The method used in implementing this community service activity is Participatory Action Research (PAR). The stages of this activity are 1). Preparation; 2). Implementation; 3). Evaluation and sustainable program planning. By teaching children aqiqah, worship and morals so that children get used to doing these things from a young age. The results of this activity are: 1). Increase awareness of parents and teachers in Hampalit Village in instilling religious values for children; 2). Provide understanding that creed is one of the important things because we believe that whatever we do there must be a reward; 3). Teach ahklak as early as possible to children so that children have a better personality.